The Relationship Between Knowledge and Role Parents in Stimulating The Development of Gross Motoric Childern Age 3-24 Months at The Cabangbungin Bekasi District Health Center Year 2022 - Een Nuraenah; Elfira Sri Futriani (Lembaga Pengembangan Kinerja Dosen, 2023)
Health development is carried out by making human resources healthy as early as possible, this is to improve the quality of life of children with optimal growth and development both physically (motor), mental, cognitive and social. The process of growth and development in children takes place very naturally, to realize children's motoric development according to their age, parents must have knowledge about child development and the role of parents in parenting to stimulate children to be confident in their basic motor development. The purpose of this study was to determine the relationship between knowledge and the role of parents in stimulating gross motor development in children aged 3–24 months. This research method uses an analytic survey with a cross sectional design. The sample in this study were parents who had children aged 3–24 months as many as 53 respondents, the sampling technique was simple random sampling. Data analysis using chi square. The results showed that there were 55.6% of parents with good knowledge and normal children's gross motor development, then 75% of parents had a good role with normal children's gross motor development. The results of the bivariate analysis of knowledge showed no significant relationship (p= 0.777), while the role of parents had a significant relationship (p = 0.002). There is a need for education and outreach to increase parental knowledge and play an involved role in stimulating children's development to achieve optimal